Goniurosaurus chengzheng sp. nov., a new species of Leopard Gecko from Guangxi, China (Squamata: Eublepharidae) - Zhu, Xiao-Yu; Liu, Yi-Jiao; Bai, Yun; Román-Palacios, Cristian; Li, Zheng; He, Zhu-Qing (Zootaxa, 2021)
Six species of geckos in the genus Goniurosaurus have been recorded from Guangxi, China. Here we describe a new species, Goniurosaurus chengzheng sp. nov. The new species is similar to allied species from Guangxi, but unique in a combination of the following characters: (1) four body bands with three between limb insertions; (2) precloacal pores 20; (3) body color reddish- brown; (4) snout to eye distance: eye to ear distance < 1. We used the mitochondrial genes 16S and cytb to confirm the distinctiveness of the species and place it within a molecular phylogeny of Goniurosaurus. The type specimens are deposited in the Museum of Biology, East China Normal University (ECNU).